Educação Ambiental no meio rural: estudo dos viveres e práticas ambientais nas escolas do campo no município de Ituiutaba-MG - Bisinoto, Cássia Maria Oliveira (2018)
Environmental Education can be applied in a variety of ways, including the purpose of building knowledge, social values, skills, attitudes and competences aimed at environmental conservation, and, in this sense, the present research aimed to understand how the transversal theme Environmental Education is being practiced in the rural schools in the municipality of Ituiutaba-MG. Specifically, we sought to analyze the Brazilian Environmental Education historically in time and space and its link with Environmental Education in rural areas. It was also verified if the environmental pedagogical practices, developed by the teachers in these schools, are in agreement with the National Curricular Parameters, specifically with regard to the Environment, in addition to identifying the connections of the way of living on farms and the pedagogical practices of Environmental Education, with respect to interdisciplinarity and transversality. Due to the unique character of the research, it was developed by means of a case study, including exploratory study, with the application of semi-structured questionnaires answered by teachers, students and their families. The analyzes indicate that environmental education practices actually take place in the rural schools, in accordance to environmental experiences, sometimes in contradiction between discourse and practice, justified by the effect of a limited participation of family and community in the school, which is a fundamental relationship for the formation of citizens as agents of change in society.